2017
DOI: 10.7754/clin.lab.2017.170313
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Insulin and Glucose on Different Characteristics of a UPEC: Alterations in Growth Rate and Expression Levels of some Virulence Genes

Abstract: In the present study, it was shown that insulin and glucose can modulate UPEC's gene expression while the growth rate was not affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
2
10
1
1
Order By: Relevance
“…Today it is well known that, the regulation of drug resistance and virulence mechanisms are tightly connected to each other [46]. In accordance with the previous studies our results show that, insulin and glucose can affect the growth and expression levels of different genes related to virulence but also antibiotic resistance [10][11][12]36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Today it is well known that, the regulation of drug resistance and virulence mechanisms are tightly connected to each other [46]. In accordance with the previous studies our results show that, insulin and glucose can affect the growth and expression levels of different genes related to virulence but also antibiotic resistance [10][11][12]36].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies suggested that, insulin-r may function as an inter-kingdom QS compound which regulates growth, biofilm formation and chemotactic responses in E. coli [10,11,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a high spread of antibiotic resistance is observed within these pathotypes [7][8][9][10][11][12]. They owe this high capacity to genetic modulate, own pathogenicity and drug resistance [13][14][15]. Several urovirulence factors, such as hemolysin (the hly gene), the cytotoxic necrotizing factor type 1 (the cnf-1 gene), the P-pili (the pap genes), S-family adhesions (the sfa gene), and the bacteriocin usp (the usp gene) are coded by the genes located on pathogenicity islands (PAIs) and through this they can be quickly transferred via the horizontal gene transfer [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Gümüş ve ark. (47) tarafından bir üropatojen E. coli suşunun üremesinin insülin varlığında değişmediği ancak 200 µU/mL insülin varlığında sfa/foc, cnf1 ve usp gibi virülans genlerinin ekspresyonlarının azaldığı bildirilmiştir.…”
Section: Grafik 6 Farklı Norepinefrin Konsantrasyonlarınınunclassified